2017
DOI: 10.1002/chem.201703598
|View full text |Cite
|
Sign up to set email alerts
|

A Platinum(II)‐based Photosensitive Tripod as an Effective Photodynamic Anticancer Agent through DNA Damage

Abstract: Herein, two photosensitive platinum(II)-based tripods were designed and synthesized. Notably, complex 1 ({[Pt(dien)] L}(NO ) , L=tri(4-pyridylphenyl)amine and dien=diethylenetriamine), which mainly accumulated in the cell nucleus, exhibited very low cytotoxicity in the absence of light irradiation, but displayed a remarkable increase in cytotoxicity upon visible light irradiation. Mechanistic investigations revealed that the tripod interacted with DNA in the nucleus, induced ROS generation upon light irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Among these, a Pt-tripod (Fig. 1a ) exhibited highly promising DNA-targeted photodynamic therapy anticancer activity both in vitro and in vivo 39 . The Pt-tripod is a three-fold-symmetric compound in a non-planar tertiary amine conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, a Pt-tripod (Fig. 1a ) exhibited highly promising DNA-targeted photodynamic therapy anticancer activity both in vitro and in vivo 39 . The Pt-tripod is a three-fold-symmetric compound in a non-planar tertiary amine conformation.…”
Section: Introductionmentioning
confidence: 99%
“…The tripodal cationic fluorescent probe NBTE was synthesized by replacing platinum(II) ligands with quaternary ammonium salt inspired by our previous work and thoroughly characterized (Figure a,b, Figures S1–S5, and Tables S1 and S2). Under physiological conditions (pH 7.4, 10 m m Tris‐HCl, 100 m m KCl), the maximum UV/Vis absorption and emission wavelength of NBTE was at 430 nm and 621 nm, respectively, with very low fluorescence quantum yield ( Φ f =0.01), and the fluorescence lifetime was short ( τ 1 /f 1 =0.1/98 %, τ 2 /f 2 =0.1/2 %) (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The digestion experiments showed that the fluorescence intensity per cell of RNase A treatment groups was 2 % of that of control groups, whereas that of DNase I treatment groups was 98 %, further validating the nuclear DNA visualization by NBTE (Figure d). The cytotoxicity assay showed that NBTE did not exhibit dark or light cytotoxicity, which was different from the tripodal platinum(II) complex with photodynamic therapy (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…By coordinating Pt(dien) (a hydrophilic platinum unit with two positive charges) on the two pyridine groups of L,t he dinuclear platinum complex, Pt 2 L (Figure 1a), with better water solubility and better affinity to negatively charged DNA, was obtained. [16] Thec ompounds L and Pt 2 L were thoroughly characterized by 1 HNMR, 13 CNMR, elemental analysis and mass spectrometry ( Figure S1-S5).…”
Section: Resultsmentioning
confidence: 99%
“…Pt 2 L showed the behavior of photoactivated escaping from autolysosomes to nucleus and interacting with DNA, which had the potential of controllable nuclear accessibility and DNAb inding with photo-selectivity to improve the treatment specificity for tumor. [5,16] To validate this,t he intracellular behavior and cytotoxicity of Pt 2 L were further investigated. By observing the intracellular distribution of Pt 2 L within 30 h, we found that Pt 2 L can effectively enter the cytoplasm of living A549 cells in 2h,a nd can remain in the cytoplasm for over 30 hw ithout entering the nucleus (Figure S18).…”
Section: Angewandte Chemiementioning
confidence: 99%